The Where and How of Clitic Order - Bonet, Eulàlia (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1995)
ABSTRACTThe main goal of this paper is to show that pronominal clitic order cannot be determined syntactically, once one explores this hypothesis taking into account not only argument-related clitics, but also inherent clitics and ethical dative clitics. Clitic order is idiosyncratic byt fixed in nature, as is shown with data coming from several dialects of Catalan. The suggestion is made that clitic order is determined post-syntactically, in the Morphology Component—see Bonet (1991, 1995), and Halle & Marantz (1993)—through the mapping onto a dialect-specific template.